ROBUST ESTIMATION OF PHARMACOKINETIC PARAMETERS IN DCE-MRI ANALYSIS OF RECTAL TUMOURS - Tanner, L; Hughes, N; Brady, M; Anderson, M; Gleeson, F; IEEE (2009)
Dynamic contrast-enhanced (DCE) MRI is a powerful tool for assessing tumour vasculature and for predicting patient response to therapy. DCE-MRI data can be quantified using pharmacokinetic models, allowing extraction of physiologically meaningful parameters. However, in clinical scans of rectal tumours many voxels within the tumour volume fail to produce valid pharmacokinetic parameters. By performing a sensitivity analysis, we find a high dependence of the model parameters on the pre-contrast relaxation time T10. Estimation of T10 is sensitive to variations in the repetition time and to the effects of patient motion. We develop a new method for incorporating variations in TR into the parameter estimation process and combine it with non-rigid image registration. Our approach offers the potential for a substantial improvement in characterisation of rectal tumours. © 2009 IEEE.